A wide-field survey for transiting hot Jupiters and eclipsing pre-main-sequence binaries in young stellar associations - Oelkers, Ryan J. (2016)
The past two decades have seen a significant advancement in the detection, classification, and understanding of exoplanets and binaries. This is due, in large part, to the increase in use of small-aperture telescopes (<20 cm) to survey large areas of the sky to milli-mag precision with rapid cadence. The vast majority of the planetary and binary systems studied to date consists of main-sequence or evolved objects, leading to a dearth of knowledge of properties at early times (<50 Myr). Only a dozen binaries and one candidate transiting Hot Jupiter are known among pre-main-sequence objects, yet these are the systems that can provide the best constraints on stellar formation and planetary migration models. The deficiency in the number of well characterized systems is driven by the inherent and aperiodic variability found in pre-main-sequence objects, which can mask and mimic eclipse signals. Hence, a dramatic increase in the number of young systems with high-quality observations is highly desirable to guide further theoretical developments. We have recently completed a photometric survey of three nearby (<150 pc) and young (<50 Myr) moving groups with a small-aperture telescope. While our survey reached the requisite photometric precision, the temporal coverage was insufficient to detect Hot Jupiters. Nevertheless, we discovered 346 pre-main-sequence binary candidates, including 74 high-priority objects for further study.